Impact of Genetic Counselling for Evaluation of Risk and Follow-Up in the Prevention and Control of Mental Illness among Antenatal Mothers - Kumar, Dr. Sikandar; Ekka, Mahlo Ansu; Kumari Devi, Sinmayee (International Journal of Innovative Research in Medical Science, 2016)
The well-being of a human being has two facets viz., physical, mental. The physical health has greater prominence over mental health aspect. The etiology of psychiatric disorder is complex, with both genetic and environmental component contributing to their development. It is thought that different set of genes may be involved in increasing susceptibility to a particular disorder in various population. Experts recommend that all pregnant women regardless of age be offered genetic counselling and testing to screen the genetic disorder and other disorders. A quantitative research approach and pre experimental design, pre-test and post-test without control group was selected for this study. The study was conducted on 50 antenatal mothers of Kalarahanga village, Bhubaneswar, Odisha through non probability purposive sampling technique. Data was collected through using a self-structured knowledge questionnaire and were analysed by using descriptive and inferential statistics. Findings revealed that there was highly significant difference in pre-test and post-test knowledge scores obtained by paired ‘t’test at 5% level of significance. Chi square test was calculated and found that there is significant association between post-test knowledge scores with education, previous knowledge and areas of living at 5% level of significance. Whereas no significant association was found between post-test knowledge scores with age, religion, parity, type of family, monthly family income, history of mental illness, history of medical diseases.. Statistical analysis of data revealed that STP was effective in improving knowledge regarding genetic counselling on mental illness among antenatal mothers.